2008
DOI: 10.1080/00016340802468316
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular enzyme glutathione S‐transferase alpha and intrahepatic cholestasis of pregnancy

Abstract: Plasma GSTA measurements may provide a more sensitive and specific diagnostic tool for diagnosis of ICP than the evaluation of transaminases or bile acid concentrations alone. Further studies are needed to evaluate the role of GSTA in the follow-up of patients with ICP and its prognostic value for threatening fetal distress in patients with ICP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A longitudinal study comparing serum levels from ICP, control and pruritus gravidarum cases demonstrated higher GSTA in ICP at all gestations from 24 wk to term [67] . A recent study confirmed that GSTA levels are elevated in ICP cases [68] , and the authors of both studies proposed that it may be a useful tool for early diagnosis of the condition.…”
Section: Lfts In Icpmentioning
confidence: 86%
“…A longitudinal study comparing serum levels from ICP, control and pruritus gravidarum cases demonstrated higher GSTA in ICP at all gestations from 24 wk to term [67] . A recent study confirmed that GSTA levels are elevated in ICP cases [68] , and the authors of both studies proposed that it may be a useful tool for early diagnosis of the condition.…”
Section: Lfts In Icpmentioning
confidence: 86%
“…Elevation of plasma level of α-GST may be an early indicator of liver damage. Different studies considered the plasma level of α-GST is an actual indicator of the integrity of the hepatocyte [19] or biomarker of liver damage, for example, in hepatic ischemia/reperfusion injury after liver resection [20], cases of rejection of liver transplant [21], liver damage after hepatectomy [22], biliary atresia [23], intrahepatic cholestasis of pregnancy [24], acute drug-induced hepatotoxicity [25], subclinical hepatic injury after anesthesia [26], hepatocellular damage during polymicrobial sepsis [27], or in patients with cystic fibrosis [28] and in chronic alcohol abusers [29]. …”
Section: Discussionmentioning
confidence: 99%